Identification, evolution, expression, and docking studies of fatty acid desaturase genes in wheat (Triticum aestivum L.) - Hajiahmadi, Zahra (BMC Genomics, 2020)
BACKGROUNDS: Fatty acid desaturases (FADs) introduce a double bond into the fatty acids acyl chain resulting in unsaturated fatty acids that have essential roles in plant development and response to biotic and abiotic stresses. Wheat germ oil, one of the important by-products of wheat, can be a good alternative for edible oils with clinical advantages due to the high amount of unsaturated fatty acids. Therefore, we performed a genome-wide analysis of the wheat FAD gene family (TaFADs). RESULTS: 68 FAD genes were identified from the wheat genome. Based on the phylogenetic analysis, wheat FADs clustered into five subfamilies, including FAB2, FAD2/FAD6, FAD4, DES/SLD, and FAD3/FAD7/FAD8. The TaFADs were distributed on chromosomes 2A-7B with 0 to 10 introns. The Ka/Ks ratio was less than one for most of the duplicated pair genes revealed that the function of the genes had been maintained during the evolution. Several cis-acting elements related to hormones and stresses in the TaFADs promoters indicated the role of these genes in plant development and responses to environmental stresses. Likewise, 72 SSRs and 91 miRNAs in 36 and 47 TaFADs have been identified. According to RNA-seq data analysis, the highest expression in all developmental stages and tissues was related to TaFAB2.5, TaFAB2.12, TaFAB2.15, TaFAB2.17, TaFAB2.20, TaFAD2.1, TaFAD2.6, and TaFAD2.8 genes while the highest expression in response to temperature stress was related to TaFAD2.6, TaFAD2.8, TaFAB2.15, TaFAB2.17, and TaFAB2.20. Furthermore, docking simulations revealed several residues in the active site of TaFAD2.6 and TaFAD2.8 in close contact with the docked oleic acid that could be useful in future site-directed mutagenesis studies to increase the catalytic efficiency of them and subsequently improve agronomic quality and tolerance of wheat against environmental stresses. CONCLUSIONS: This study provides comprehensive information that can lead to the detection of candidate genes for wheat genetic modification. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-020-07199-1.